2007
DOI: 10.1590/s1415-43662007000200005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do uso de fertilizantes organominerais e químicos na fertirrigação do cafeeiro irrigado por gotejamento

Abstract: Com o objetivo de avaliar a fertirrigação do cafeeiro com a utilização de diferentes fontes de fertilizantes, instalou-se um experimento na Fazenda Escola da Universidade de Uberaba, em Latossolo Vermelho Amarelo textura arenosa, a 850 m de altitude, em lavoura de café Catuaí Vermelho IAC 144. Foram aplicados os seguintes tratamentos: adubação de cobertura convencional química; adubação de cobertura com adubos sólidos convencionais, via fertirrigação; adubação de cobertura com adubos próprios para fertirrigaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
1
9
0
4
Order By: Relevance
“…In a Latossolo Vermelho-Amarelo, i.e., a Rhodic Hapludox, with a sandy texture, Fernandes et al (2007) found no significant differences in coffee (Coffea arabica L.) yield in response to the use of organominerals in solid form and poultry litter-based, when compared with conventional chemical sources. Similarities in crop yield have also been observed between other organic materials and mineral sources in fertilizer formulation (Tejada et al, 2004;Babalola et al, 2007).…”
Section: Resultsmentioning
confidence: 88%
“…In a Latossolo Vermelho-Amarelo, i.e., a Rhodic Hapludox, with a sandy texture, Fernandes et al (2007) found no significant differences in coffee (Coffea arabica L.) yield in response to the use of organominerals in solid form and poultry litter-based, when compared with conventional chemical sources. Similarities in crop yield have also been observed between other organic materials and mineral sources in fertilizer formulation (Tejada et al, 2004;Babalola et al, 2007).…”
Section: Resultsmentioning
confidence: 88%
“…This may have occurred as a result of the benefits of the organomineral fertilizer in terms of providing nutrients (FERNANDES et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the organomineral fertilizers presented good results in agriculture, improving the efficiency of the plant uptake and reducing the use of chemical fertilizers and production costs (FERNANDES et al, 2007). Organomineral fertilizers contain sources of both organic and chemical fertilizers, which helps reduce nutrient losses by increasing the proliferation of microorganisms and the use of fertilizer in the soil, which represents a significant reduction in costs to farmers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma destas práticas é a fertirrigação, que tem sido utilizada com frequência pelos cafeicultores irrigantes, em especial por aqueles que dispõem de sistemas de irrigação por pivô central e gotejamento (FERNANDES et al, 2007).…”
Section: Irrigação E Fertirrigação Na Cultura Do Café Conilonunclassified